Longevity of direct diastema closure and recontouring restorations with resin composites in maxillary anterior teeth: A 4-year clinical evaluation - KORKUT, BORA; TÜRKMEN, CAFER (WILEY, 2021)
Objectives To evaluate the clinical performance of resin composite restorations and to investigate causes of failure. Materials and Methods The longevity of 216 restorations in 53 patients (mean age, 33.3 years) was retrospectively evaluated according to Federation Dentaire Internationale (FDI) criteria. Dental history and photographic data were used to evaluate diastema closure (n = 199) and recontouring (n = 19) restorations comprising microhybrid (Essentia Universal, GC Corp.), nanohybrid (Ceram.x One, Dentsply Sirona), and nanofilled (Estelite Asteria, Tokuyama Dental) composites. Data were analyzed with the Kaplan-Meier log-rank test, Cox regression analysis, Pearson chi-square test. p < 0.05 was considered statistically significant. The overall survival rate was 90.3 % and the mean survival duration was 46.2 months during the for 4 - year study period. The annual failure rate was 0.9 % - 3.4 %. Mean survival durations for diastema closure and recontouring restorations were 46.2 and 45.9 months, respectively (p = 0.328). Mean survival durations for Essentia Universal, Estelite Asteria, and Ceram.x One were 46.1, 46.7, and 45.7 months, respectively (p = 0.677). If we include failed restorations that were repaired and remained functional, the overall survival rate was 100 %. Conclusion Longevity was similar among composites and restoration types. The long-term clinical performance of monochromatic anterior composite restorations was robust. Composite repair may be suitable for diastema closure and recontouring restorations. Clinical Significance There is a lack of long-term clinical evidence regarding the performance of direct anterior composite restorations. Monochromatic direct composite restorations may meet both the esthetic and functional expectations with even simpler restorative techniques. This 4 - year follow-up study evaluated the clinical performance of monochromatic anterior diastema closure and recontouring restorations with three different composite materials. The longevity of the restorations and the reasons for failure were investigated.
Keywords: composite; diastema closure; longevity; microhybrid; nanohybrid; CLOSING DIASTEMAS; SURVIVAL; PERFORMANCE; ROUGHNESS; BUILDUPS; VENEERS